2006
DOI: 10.1111/j.1525-1438.2006.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography as a diagnostic aid to visual inspection and colposcopy for preinvasive and invasive cancer of the uterine cervix

Abstract: The purpose of this study was to determine the sensitivity and specificity of optical coherence tomography (OCT) under two well-defined clinical settings. First, as an aid to cervical cancer screening, using visual inspection with acetic acid (VIA) in low-resource settings, and the second, as an adjunct to the traditional management of abnormal cervical cytology with colposcopy and biopsy. Patients referred for colposcopy with > or = atypical squamous cells of undetermined significance were accrued for the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
6

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 17 publications
1
40
0
6
Order By: Relevance
“…OCT has previously been used in a variety of applications, including human eye, 11,12 gastrointestinal neoplasms, 13,14 and gynecologic neoplasms such as ovary, [15][16][17][18][19] endometrium [18][19][20] and cervix. 18,19,[21][22][23][24][25][26] Prior studies evaluating OCT imaging of human ovarian tissue have shown promising results as a diagnostic tool for ovarian cancer, demonstrating the ability to visualize fine architectural features of both normal ovaries and ovarian malignancies ex vivo [16][17][18] and in vivo via laparoscopic imaging. 15,19 Laser-induced fluorescence (LIF) spectroscopy is another non-destructive imaging modality with promising diagnostic capabilities in ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
“…OCT has previously been used in a variety of applications, including human eye, 11,12 gastrointestinal neoplasms, 13,14 and gynecologic neoplasms such as ovary, [15][16][17][18][19] endometrium [18][19][20] and cervix. 18,19,[21][22][23][24][25][26] Prior studies evaluating OCT imaging of human ovarian tissue have shown promising results as a diagnostic tool for ovarian cancer, demonstrating the ability to visualize fine architectural features of both normal ovaries and ovarian malignancies ex vivo [16][17][18] and in vivo via laparoscopic imaging. 15,19 Laser-induced fluorescence (LIF) spectroscopy is another non-destructive imaging modality with promising diagnostic capabilities in ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the sensitivity and specificity of (traditional) colposcopy for lesions ‡CIN2 in this study are 39% (95% CI 24-57) and 71% (95% CI 64-77), respectively, while the sensitivity and specificity of blinded OCT for this diagnosis are 56% (95% CI 39-72) and 59% (95% CI 52-66), respectively. 64 The sensitivity and specificity of colposcopy and OCT together for diagnosing HG lesions are 46% (95% CI 30-64) and 69% (95% CI 62-75), respectively. 64 So, this study suggests that OCT can improve the sensitivity of the colposcopic examination at a cost of a slightly lower specificity.…”
Section: Optical Coherence Tomographymentioning
confidence: 97%
“…60,61 Since OCT is capable of providing images of tissue structures at a cellular level with a resolution of 10-20 mm, this technique holds promise for diagnosing cervical lesions without having to take a biopsy ('optical biopsy'). 59,[62][63][64][65] One study has been conducted to determine the sensitivity and specificity of OCT in which this technique is used as an adjunct to the traditional management of abnormal cytology with colposcopy and biopsy. 64 After completion of the examinations, all the OCT images were reviewed twice.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] To attempt to fight the HIV epidemic, microbicides, vaginal products for prevention of acquisition of the infection, have been developed. However, some of these products have been toxic to the genital tract, and more specifically, the cervicovaginal tract, and have increased or failed to prevent transmission of HIV.…”
Section: Introductionmentioning
confidence: 99%